Revision of the genus Morphosphaera Baly (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng; Bezdĕk, Jan (Zootaxa, 2016)
The genus Morphosphaera Baly, 1861 is revised. Eleven species are considered as valid, including, M. takizawai sp. nov. (Mt. Basor, 90 km N of Gua Musang, Malaysia, W. Kelantan), described from Malaysia and Indonesia. Color photos of habitus and drawings of diagnostic characters from eleven species are presented. The following synonymies are proposed: M. sodalis Chen, 1935 and M. brunnea Maulik, 1936 are junior synonyms of M. albipennis Allard, 1889; M. margaritacea Laboissière, 1930, M. viridipennis Laboissière, 1930, and M. prava Maulik, 1936 are junior synonyms of M. coomani Laboissière, 1930; M. gracilicornis Chen, 1963 is a junior synonym of M. maculicollis Baly, 1861; M. cavaleriei Laboissière, 1930, M. cincticollis Laboissière, 1930, M. marginata Laboissière, 1930, M. purpurea Laboissière, 1930, M. gingkoae Gressitt & Kimoto, 1963, and M. metallescens Gressitt & Kimoto, 1963 are junior synonyms of M. sumatrana Jacoby, 1886. The type material of M. impunctata Allard, 1890 from the Philippines was not found and its taxonomic status remains uncertain. Morphosphaera peregrina Weise, 1913 is transferred to the genus Borneola Mohamedsaid, 1998 nov. comb. A neotype is designated for Chrysomela japonica Hornstedt, 1788. Lectotypes are designated for the following species: Adorium chrysomeloides Bates, 1866, A. japonicum Baly, 1874, Morphosphaera albipennis Allard, 1889, M. bimaculata Chûjô, 1938, M. caerulea Jacoby, 1896, M. cavaleriei Laboissière, 1930, M. collaris Laboissière, 1930, M. formosa Laboissière, 1930, M. marginata Laboissière, 1930, M. montivaga Maulik, 1936, M. prava Maulik, 1936, M. purpurea Laboissière, 1930, M. sumatrana Jacoby, 1886, M. viridipennis Laboissière, 1930, and Galerucida simplex Weise, 1922.